Novel excitation-contraction coupling related genes reveal aspects of muscle weakness beyond atrophy—new hopes for treatment of musculoskeletal diseases - Manring, Heather; Abreu, Eduardo; Brotto, Leticia; Weisleder, Noah; Brotto, Marco (Frontiers in Physiology, 2014)
Research over the last decade strengthened the understanding that skeletal muscles are not only the major tissue in the body from a volume point of view but also function as a master regulator contributing to optimal organismal health. These new contributions to the available body of knowledge triggered great interest in the roles of skeletal muscle beyond contraction. The World Health Organization, through its Global Burden of Disease (GBD) report, recently raised further awareness about the key importance of skeletal muscles as the GDB reported musculoskeletal (MSK) diseases have become the second greatest cause of disability, with more than 1.7 billion people in the globe affected by a diversity of MSK conditions. Besides their role in MSK disorders, skeletal muscles are also seen as principal metabolic organs with essential contributions to metabolic disorders, especially those linked to physical inactivity. In this review, we have focused on the unique function of new genes/proteins (i.e. MTMR14, MG29, sarcalumenin, KFL15) that during the last few years have helped provide novel insights about muscle function in health and disease, muscle fatigue, muscle metabolism, and muscle aging. Next, we provide an in depth discussion of how these genes/proteins converge into a common function of acting as regulators of intracellular calcium homeostasis. A clear link between dysfunctional calcium homeostasis is established and the special role of store-operated calcium entry is analyzed. The new knowledge that has been generated by the understanding of the roles of previously unknown modulatory genes of the skeletal muscle excitation-contraction coupling (ECC) process brings exciting new possibilities for treatment of MSK diseases, muscle regeneration, and skeletal muscle tissue engineering. The next decade of skeletal muscle and MSK research is bound to bring to fruition applied knowledge that will hopefully offset the current heavy and sad burden of MSK diseases on the